Managerial Process and Organizational Behavior - Ladouceur, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Managerial Process and Organizational Behavior" by Alan C. Filley and Robert J. House-Scott.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z